Clinical Profile of Primary Central Nervous System Demyelinating Disorders: A Tertiary Care Hospital-Based Study in Guwahati - Manisha Manisha; Anirban Mahanta; Munindra Goswami; Marami Das (Indian Journal of Medical Specialities)
Background: The primary central nervous system (CNS) demyelinating disorders are witnessing significant advancement in terms of treatment options and the diagnostics. However, a resource poor country like ours has to rely more on our clinical findings. Aims and Objectives: To study the spectrum of different clinical manifestations in patients of various primary CNS demyelinating disorders in the hospital setting; categorizing them to the most possible extent into its various types viz. multiple sclerosis(MS), neuromyelitis optica spectrum disorder (NMOSD), acute disseminated encephalomyelitis(ADEM), idiopathic optic neuritis(ON). Metarials and Methods: An observational study was conducted for 2 years including old and newly diagnosed cases in whom detailed clinical assessment was done for every attack including the previous and subsequent ones. Statistical analysis was done using SPSS version 21. Results: Of the 47 patients included, 26 (55.3%) were cases of NMOSD, 12 (25.5%) of MS, 4 (8.5%) of ADEM and 5 (10.6%) were isolated cases of ON. 30 were female and 17 were male (ratio 1:0.6). The total mean age for primary CNS demyelinating disorders at presentation was 27.09 ± 13.44 years. Maximum patients fell in the age range of 11–20 years. Among the clinical manifestations, motor abnormalities (97.6%), sensory abnormalities (69%), bladder dysfunction (59.5%), visual manifestations (54.8%) (Unilateral in all MS patients, both bilateral and unilateral in NMOSD) were the most common presentations. In MS, the most common manifestations were motor dysfunction followed by sensory symptoms, optic neuropathy (mostly unilateral), and bladder dysfunction. In NMOSD, the most common clinical manifestations were motor dysfunction, followed by bladder dysfunction, optic neuropathy and then sensory abnormalities. In ADEM, most common manifestations were motor abnormalities, acute encephalopathy, headache, optic neuropathy. Among idiopathic ON, most patients presented with painful diminution of vision (80%). Mean number of attacks was 2.53. Conclusion: A wide spectrum of clinical presentations in various disorders of primary CNS demyelination was found with maximum patients presenting with motor dysfunction in various forms.